At the center feminism, social science and knowledge - Demos, Vasilikie P.; Segal, Marcia Texler, 1940- (Bingley, U.K. : Emerald, 2015)
At the center reflects on how the study of gender has changed and how studying gender has affected our research methods and our knowledge of the world around us. In honor of Bell Hooks' prophetic work, Feminist theory : from margin to center, the volume considers how advances in gender research represent a centering of feminist knowledge and an understanding of the process by which feminist knowledge is constructed. A multinational group of contributors explore relatively new problems such as the integration of transgender study, traditional topics in so far as they incorporate current knowledge and methodological issues pertaining to the effects of research on the researcher and the researched as well as other epistemological matters associated with the construction of gender knowledge. Chapters reflect the strength of a range of qualitative methods including life histories and autoethnography and explore the ways that large sample quantitative analyses can enhance understanding of everyday dilemmas. The interdisciplinary nature of gender studies and the crosspollination of theoretical perspectives are illustrated as is the globalization of gender theory, research and policies.
At the center : feminism, social science and knowledge : an overview of this volume / Marcia Texler Segal, Vasilikie Demos -- Twenty volumes of feminism at the center of social science and knowledge / Marcia Texler Segal, Vasilikie Demos -- Beyond inclusion : thinking toward a transfeminist methodology / Austin H. Johnson -- Recent advances in feminist science and technology studies : reconceptualizing subjectivity and knowledge / Landon Schnabel, Lindsey Breitwieser -- Choosing submission : advances in understanding agency and embodiment / Nichole Edwards -- Age and gender discrimination : intersecting inequalities across the lifecourse / Catherine E. Harnois -- More than a war story : a feminist analysis of doing dangerous fieldwork / Jennifer B. Rogers-Brown -- Womanhood and motherhood renegotiated through transnational adoption / Jennifer Rothchild -- Engendering justice : dismantling essentialisms of gender and sexual violence in Yogyakarta / Alice J. Peck -- Gender mainstreaming and womens roles in development projects : a research case study from Ghana / Kwadwo AduseiAsante, Peter Hancock, Max Oliveira -- Beyond classroom knowledge and experience : how can fieldwork enrich students learning and perception on gender? / Sara Nuzhat Amin ... [et al.] -- Feminist pedagogy and research in a culturally diverse classroom in a women's university in Bangladesh / Meghan Daniel, Cleonicki Saroca -- Metaphors on women in academia : a review of the literature, 2004-2013 / Fran Amery ... [et al.] -- The gendering of immigration studies in the United States / Chien-Juh Gu -- The unread red feminists : silenced precursors of the U.S. second wave / Susan Archer Mann.
Print version record
Keywords: Social Science -- Gender Studies; Social Science -- Feminism & Feminist Theory; Gender studies: women; Feminism & feminist theory; Feminism -- Research; Feminism -- Social aspects; Women's studies